"RFLP" analysis of aluminum tolerance in chromosome 2 in maize - Brondani, Claudio; Paiva, Edilson (Pesquisa Agropecuaria Brasileira, 1996)
This paper aimed to look for genomic regions related with the aluminum tolerance in chromosome 2 of maize using the RFLP technique. Four aluminum tolerant maize lines (15, 16, 699 and 1327) and three non-tolerant ones (19, 53 and 57) were crossed: 57 x 1327, 57 x 699, 53 x 16, 53 x 15 and 19 x 1327. The degree of tolerance to aluminum of the parents, F1's and F2 were determined through measurements of the Relative Seminal Root Length of seedlings grown in nutrient solution containing 222 µmol of Al/L. The RFLP analysis was made in the 6 more tolerant F2 plants and in the 6 more susceptibles plants of each cross, testing two restriction enzymes and five probes from different regions of chromosome 2 of maize, which have loci to Al tolerance. Tolerant and susceptible RFLP different markers were identified to each cross. These markers are potentially useful in marker assisted selection with RFLP's in the genetic breeding for Al tolerance in maize.